Aplikasi Berbasis Web Pengelolaan Pembiayaan Kegiatan Santri Menggunakan Metodologi Rasional Unified Process - Rahayu, Raden Erwin Gunadhi; Latifah, Ayu; Azmi, Muhammad (Institut Teknologi Garut, 2025)
Advances in information and communication technology have affected various sectors, including educational institutions such as Islamic boarding schools. Nurul Hikam Asy-Syarifiah boarding school, located in Garut, faces challenges in managing information regarding the financing of santri activities. This research aims to design a web-based application to improve the transparency of the management of student activity financing at the boarding school. The Rational Unified Process (RUP) methodology was used with the Laravel framework, PHP, and MySQL. The results show that this application makes it easier for parents of students to prepare budgets through structured billing information. The main contribution is an information technology solution to overcome financial management challenges in traditional educational institutions.